Rancang Bangun Alat Pengkalis Adonan Kerupuk Krecek untuk Meningkatkan Kualitas Adonan dan Produktivitas pada UMKM Kerupuk Krecek di Nganjuk - Kurniwan, Mohammad Ilham; Satoto, Handy Febri (SURYA TEKNIKA, 2025)
MSMEs Kerupuk Krecek Pak Sholeh in Kediri produces starch crackers with a Make To Stock system and distribution to Madiun, Magetan, and Tulungagung. Production reaches 3750 kg per month, but is constrained by the dough rolling process which still uses a simple multifunction machine. This machine is not specifically designed, so it produces inconsistent dough, extends production time, and reduces product quality. To overcome this, a special dough rolling machine was designed based on ergonomics, productivity, and anthropometry approaches. This machine uses a stable drive motor that produces dough that is elastic, smooth, and even without lumps. Kneading time is also reduced from 30-40 minutes to only 15-20 minutes. In addition to increasing efficiency, the design of the container and roll minimizes material loss and makes cleaning easier. This machine is able to improve the quality, process efficiency, and productivity of MSMEs Kerupuk Krecek as a whole.